Clinical predictors and concomitant antiseizure medications effects on seizure control in relation to plasma cenobamate concentration: a multicenter retrospective study - Operto, Francesca Felicia; Izzo, Viviana; Assenza, Giovanni; Balsamo, Anna Chiara; Canafoglia, Laura; Cerulli Irelli, Emanuele; Coglianese, Albino; Di Bonaventura, Carlo; Gambardella, Antonio; Liguori, Claudio; Pastorino, Grazia Maria Giovanna; Pezzella, Marianna; et al. (Frontiers in Pharmacology, 2025)
IntroductionCenobamate (CNB) is a novel antiseizure medication (ASM) approved as an add-on therapy for drug-resistant focal onset seizures. Although its mechanism of action is not fully understood, CNB enhances inhibitory GABAergic transmission and blocks voltage-gated sodium channels. Its non-linear pharmacokinetics and strong modulation of cytochrome P450 enzymes may significantly affect the metabolism of co-administered ASMs, posing important challenges for polytherapy management. This retrospective study, complemented by prospective follow-up evaluations, aimed at elucidating, in a cohort of subjects enrolled in an Italian multicenter study, the following: i) the CNB dose associated with clinical response; ii) inter-individual variability in CNB plasma concentrations (CNBp); iii) the potential correlation between CNBp and clinical features including age, sex and body mass index (BMI); iv) interactions between CNB and co-administered ASMs.MethodsWe enrolled 53 adults with drug-resistant focal epilepsy, who started CNB with titration to 200 mg/day, were monitored monthly, and classified as responders (≥50% seizure reduction) or non-responders (<50%). In responders, plasma CNB concentration (CNBp) was measured at the time of their first documented clinical response. Multiple linear regression, including covariates such as age, sex, BMI, CNB dose, and co-administered ASMs, was applied to assess independent predictors of CNBp.ResultsA clinical response was achieved in 26/53 (49%) subjects. Among responders, 53.8% (14/26) achieved response on ≤100 mg/day, with CNBp of 0.5–17.6 μg/mL (median ∼5–6 μg/mL). There was no significant relationship between age and gender, although there was a statistically significant correlation between CNBp and BMI (p = 0.038; R2 = 0.157). In subjects co-administered benzodiazepines, zonisamide, phenobarbital, and perampanel, higher CNBp were observed; conversely, lower CNBp were linked to brivaracetam, topiramate, lamotrigine, and levetiracetam. Additionally, a modest decrease in CNBp was associated with carbamazepine, consistent with its known enzyme-inducing effect.DiscussionThese findings suggest that CNB may achieve clinically meaningful seizure control at relatively low doses, with variability in plasma concentrations largely influenced by concomitant medications and, to a lesser extent, by individual characteristics. Despite the limited sample size, our results highlight the value of therapeutic drug monitoring and individualized titration to optimize CNB therapy in drug-resistant focal epilepsy.